Individualized techniques of implant coating with an antibiotic-loaded, hydroxyapatite/calcium sulphate bone graft substitute - Freischmidt, Holger; Armbruster, Jonas; Reiter, Gregor; Grützner, Paul Alfred; Helbig, Lars; Gühring, Thorsten (Therapeutics and clinical risk management, 2020)
Background - The treatment of fracture- or non-union-related infections has persistently been a major challenge for both patients and treating surgeons. With rising aging of patients and increasing comorbidities, combined with the heterogeneity of germs and any number of multi-resistance against standard antibiotics, a successful treatment is increasingly difficult. One potential solution could be a custom-made individualized antibacterial coating of standard implants with a biphasic degradable biocarrier (Cerament G/V, supplied by Bonesupport AB, Lund, Sweden) that releases high doses of antibiotics around the bone-implant-interface. Here, we describe our technique of coating intramedullary nails, plates and press-fit shoulder endoprostheses which may prevent bacterial adhesion and biofilm formation. So far, there is very limited experience in individual coating of implants in hip or knee endoprostheses to prevent reoccurrence of surgical-site infection. Currently, no reports are available for coating of stems of shoulder prosthesis and nails or plates for fracture fixation. - - Methods - Here, we show our first experiences with a new individualized surgical technique of coating these implants with a resorbable antibiotic-loaded hydroxyapatite/calcium sulphate biocomposite to prevent biofilm formation and thereby recurrence of bone or joint infection. We describe three cases for coating of plates and nails for fracture fixation and coating of stems of a shoulder prosthesis. - - Results - No adverse events of the resorbable bone graft substitute were observed. In all of the cases, no recurrence of the infection was observed and osseointegration was achieved. After implant coating of the shoulder prosthesis, no radiological signs of loosening were detected. - - Conclusion - We present a new surgical approach of a surface coating of plates, intramedullary nails or prostheses. The osteoconductive- and anti-inflammatory effect of the gentamicin- or vancomycin-loaded hydroxyapatite/calcium sulphate bone graft substitutes shows promising results.
Gesehen am 02.10.2020